2019
DOI: 10.1089/cbr.2018.2697
|View full text |Cite
|
Sign up to set email alerts
|

miR-4429Inhibits Tumor Progression and Epithelial-Mesenchymal Transition Via TargetingCDK6in Clear Cell Renal Cell Carcinoma

Abstract: Background: Clear cell renal cell carcinoma (ccRCC), as the commonest type among renal cell cancers, is featured with easy relapse and metastasis. Despite mounting achievements on its treatment and diagnosis, the identification of new biomarkers remains urgent. Purposes: Present study aimed to explore the role of microRNA-4429 (miR-4429) in ccRCC. Methods: The expression of miR-4429 and cyclin-dependent kinase 6 (CDK6) was evaluated by real-time polymerase chain reaction and Western blot. Cell proliferation, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 26 publications
2
18
0
Order By: Relevance
“…It was found that miR-4429 targeted DLEU1 in GBM cells. MiR-4429 was demonstrated in previous work to act as an anti-tumor miRNA, such as clear cell renal cell carcinoma [46] and papillary thyroid cancer [47]. Our study uncovered that inhibition of miR-4429 aggravated GBM cell growth, consolidating its tumor-suppressive role in GBM.…”
Section: Discussionsupporting
confidence: 53%
“…It was found that miR-4429 targeted DLEU1 in GBM cells. MiR-4429 was demonstrated in previous work to act as an anti-tumor miRNA, such as clear cell renal cell carcinoma [46] and papillary thyroid cancer [47]. Our study uncovered that inhibition of miR-4429 aggravated GBM cell growth, consolidating its tumor-suppressive role in GBM.…”
Section: Discussionsupporting
confidence: 53%
“…MiR-4429 promotes cervical cancer cell radio-sensitivity through RAD51 [26]. MiR-4429 suppresses cell proliferation, migration, invasion, and EMT via modulating CDK6 in clear cell renal cell carcinoma [27]. Furthermore, miR-4429 was proved to be sponged and negatively regulated by NR2F2-AS1 in cervical cancer.…”
mentioning
confidence: 97%
“…miR‐4429 has been reported to be downregulated and functioned as a tumor‐suppressor gene in papillary thyroid cancer (W. J. Wu et al, ). Furthermore, the antioncogenic role of miR‐4429 has been verified in clear cell renal cell carcinoma via targeting CDK6 (Pan, Hong, Yu, Li, & Zhang, ). In concordance, present study first identified that miR‐4429 was downregulated in CC cell lines compared with normal cell line.…”
Section: Discussionmentioning
confidence: 99%